Surface-bound reactive oxygen species generating nanozymes for selective antibacterial action - Feng Gao (Nature Portfolio, 2021)
Nanozymes have been used for antibacterial applications but have potential toxicity to mammalian cells. Here the authors suggest that nanozymes that generate surface bound reactive oxygen species disrupt bacterial cell walls but not mammalian cells walls due to the different particle uptake mechanisms.